Sustainability of Diets in Mexico: Diet Quality, Environmental Footprint, Diet Cost, and Sociodemographic Factors - Curi-Quinto, Katherine; Unar-Munguía, Mishel; Rodríguez-Ramírez, Sonia; Rivera, Juan A.; Fanzo, Jessica; Willett, Walter; Röös, Elin (Frontiers in Nutrition, 2022)
Background: Little is known about the current intake of sustainable diets globally and specifically in middle-income countries, considering nutritional, environmental, and economic factors. Objective: To assess and characterize the sustainability of Mexican diets and their association with sociodemographic factors. Design: Dietary data of 2438 adults within the National Health and Nutrition Survey 2012 by integrating diet quality measured by the Healthy Eating Index (HEI-2015), diet cost, and four environmental indicators were analyzed: land use (LU), biodiversity loss (BDL), carbon footprint (CFP), and blue water footprint (BWFP). We defined healthier more sustainable diets (MSD) as those with HEI-2015 above the overall median, and diet cost and environmental indicators below the median. Logistic regression was used to evaluate the association of sociodemographic factors with MSD. Results: MSD were consumed by 10.2% of adults (4% of urban and 22% of rural), who had a lower intake of animal-source foods, unhealthy foods (refined grains, added sugar & fats, mixed processed dishes, and sweetened beverages), fruits, and vegetables, and higher intake of whole grains than non-MSD subjects. Characteristics of MSD vs. non-MSD (urban; rural) were: HEI-2015 (62.6 vs 51.9; 66.8 vs 57.6), diet-cost (1.9 vs 2.8; 1.9 vs 2.5 USD), LU (3.3 vs 6.6; 3.2 vs 5.9 m2), BDL (105 vs 780; 87 vs 586 species x 10-10), BWFP (244 vs 403; 244 vs 391 L), and CFP (1.6 vs 4.4; 1.6 vs 3.7 kg CO2eq). Adults from rural vs urban (OR 2.7; 95% CI: 1.7, 4.1), or from the South (OR 2.1; 95% CI: 1.1, 3.9), Center (OR 2.3; 95% CI: 1.3, 4.4) vs the North were more likely to consume MSD, while adults with high vs low socioeconomic status were less likely (OR 0.17; 95% CI: 0.09, 0.3). Conclusions: The MSD is a realistic diet pattern mainly found in disadvantaged populations, but diet quality is still sub-optimal. Increased consumption of legumes, fruits, and vegetables, and a reduction in unhealthy foods, are required to improve the nutritional quality of diets while ensuring their environmental sustainability.